Renovation of large-panel buildings in context of urban renewal = Remonty budynków wielkopłytowych, jako element rewitalizacji miast - Ligęza, Wiesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents issues connected with renovating multi-storey precast concrete buildings, resulting from the consequences of construction defects occurring over the course of the building process and use of the buildings, as well as design flaws and construction defects when insulating external partitions.
Keywords: budownictwo wielkopłytowe; prefabrykaty; remonty; rewitalizacja; large-panel building; precast concrete; revitalisation